Future projection of extremely hot and precipitation events over Southeast Asian river basins under RCP8.5 scenario. (27th October 2021) - Nath, Reshmita; Luo, Yong
Abstract: Southeast Asian (SEA) river basins, particularly Huang He, Yangtze and Mekong river basins, are home for large share of global population. The region is experiencing rapid socio‐economic development, urbanization and industrialization. Using Community Earth System Model large ensemble data, seasonal mean surface air temperature (SAT) in summer is projected to increase by ~6°C under Representative Concentration Pathway (RCP) 8.5 scenario. As a consequence, in the long term (2071–2100), record‐breaking extreme hot and precipitation events are projected to increase by ~90–100% and ~ 60–70%, respectively. The climate mean SAT will increase by 4 ~ 5.5°C by the end of 21st century. Extreme events occur due to the combined influence of external forcing factors and internal variability. The relative strength of both the factors are estimated by signal‐to‐noise ratio (SNR), that is, the ratio of external forcings and internal variability. Until 2000/1998/2000, SNR < 1 over Huang He/Yangtze/Mekong river basins, that is, internal variability dominates over external forcings, while from 2001/1999/2001 onwards, SNR > 1, that is, external forcings strongly override the internal climate variability. Interestingly, the SAT variability at 50th (mean state) and 95th (record‐breaking hot/wet extreme) percentile will decrease significantly as climate warms in the future. It contradicts the existing hypothesis that as the climate warms in the future, variability will increase and weather will get more volatile everywhere. Interestingly, in our analysis, SAT variability appears to decrease over SEA river basins, which is opposite to the current understanding. It makes the result a novel one. We analyse the temperature–precipitation relationship under RCP8.5 scenario, which displays a peak‐shaped structure, that is, precipitation is increasing at low–mid‐range of temperature rise, while it decreases at higher temperatures. Abstract : In long term, extremely hot and precipitation events over Southeast Asian river basins will increase by ~90–100% and ~ 60–70%, respectively. The mean surface temperature will increase by 4.15–5.35°C. SAT variability will decrease in SEA river basins as the climate warms, which is opposite to the current understanding and makes the result a novel one. The temperature–precipitation relationship under RCP8.5 scenario display peak‐shaped structure, that is, precipitation increases at low–mid‐range of temperature rise, while it decreases at higher temperatures.